Mitochondrial replication's role in vertebrate mtDNA strand asymmetry - André Gomes-dos-Santos; Nair Vilas-Arrondo; André M. Machado; Esther Román-Marcote; Jose Luís Del Río Iglesias; Francisco Baldó; Montse Pérez; Miguel M. Fonseca; L. Filipe C. Castro; Elsa Froufe (Open Biology, 2023)
Mitogenomes are defined as compact and structurally stable over aeons. This perception results from a vertebrate-centric vision, where few types of mtDNA rearrangements are described. Here, we bring a new light to the involvement of mitochondrial replication in the strand asymmetry of the vertebrate mtDNA. Using several species of deep-sea hatchetfish (Sternoptychidae) displaying distinct mtDNA structural arrangements, we unravel the inversion of the coding direction of protein-coding genes (PCGs). This unexpected change is coupled with a strand asymmetry nucleotide composition reversal and is shown to be directly related to the strand location of the Control Region (CR). An analysis of the fourfold redundant sites of the PCGs (greater than 6000 vertebrates), revealed the rarity of this phenomenon, found in nine fish species (five deep-sea hatchetfish). Curiously, in Antarctic notothenioid fishes (Trematominae), where a single PCG inversion (the only other record in fish) is coupled with the inversion of the CR, the standard asymmetry is disrupted for the remaining PCGs but not yet reversed, suggesting a transitory state. Our results hint that a relaxation of the classic vertebrate mitochondrial structural stasis promotes disruption of the natural balance of asymmetry of the mtDNA. These findings support the long-lasting hypothesis that replication is the main molecular mechanism promoting the strand-specific compositional bias of this unique and indispensable molecule.